Chemical composition of Corymbia citriodora - ABDULRAHMAN MAHMOUD DOGARA (Smujo International, 2023)
Abstract. Dogara AM. 2023. Chemical composition of Corymbia citriodora. Nusantara Bioscience 15: 172-178. Aromatic plants, particularly those in the Myrtaceae family, are widely used both traditionally and commercially to lengthen food's shelf life and safety. The current investigation was prompted by a lack of information on the composition of the plant's oil, which has traditionally been used to treat and manage cancer, malaria, typhoid fever, and various other ailments. The study thoroughly examines the chemical composition of the essential oil obtained from Corymbia citriodora (Hook.) K.D.Hill & L.A.S.Johnson. Hydro distillation was used to extract essential oil from the leaves, which were then analyzed using gas chromatography coupled with mass spectrometry. Fourier Transform Infrared spectroscopy (FTIR) was used to identify the functional group in the essential oil. According to the findings, monoterpene compounds make up (0.8137%), sesquiterpenoids (0.6568%) and other compounds (95.7207% of the total). The most abundant substance was 1-Octadecene (7.83%), followed by Oleic acid, 9-Octadecenoic acid, (E)-, (6.16%), Octadecanal, Disparlure, and 1-Octadecene (all of which were at or below 4%), and all other substances. The C. citriodora essential oil yielded 11 spectra. The extracts had sharp peaks at 900 cm-1 (phenyl), 1400 (mono-, oligo-, and carbohydrates), and 2900 (lipid methoxy compounds of CH3 and CH2, which have distinctive C-H stretching vibrations). OH groups from water, alcohols, phenols, polysaccharides, and peroxides are fingerprinted at 3400 cm-1. The study concludes that oleic acid-rich oil from C. citriodora leaves could be used as an economical source of oleic acid; the study lays the groundwork for future research on the plant in this issue.